Synthesis and Structural Analysis of High Strength Composite Flexible Landing Gear Legs - Borkowski, Paweł; Dacko, Adam; Rodzewicz, Mirosław (Proceedings of the 13th International Scientific Conference, 2017)
The problem considered was to develop, synthesize and design a flexible landing gear leg, subject to some restrictions resulting from requested loads and boundary conditions. The problem was already undertaken by many researchers, e.g. in monographs written by Currey (Aircraft Landing Gear Design: Principles and Practices, 2004, 1) and Thuis (The development of composite landing gear components for aerospace applications, 2004, 2) and in journals and conference papers (Ganorkar and Deshbhratar, Design Optimization of landing gear of an aircraft, 2014, 3; Goyal and Laksminarayan, Design, Analysis and Simulation of a composite main landing gear for a light aircraft, 2002, 4; Yu-xiu et al., The dynamics research on the composite undercarriage of the Unmanned Aerial Vehicle, 2015, 5; Niezgoda et al., Selection of dynamics characteristics for landing gear with the use of numerical model, 2002, 6). It was assumed that two roving “concentrated constant cross-section booms” would be created. FE simulations allowed to determine the flexible leg deformations, stress distribution and Failure Indices (using maximum stress theory) (Spencer, Novel Optimization Strategy for Composite Beam Type Landing Gear for Light Aircraft, 2013, 7). The foam core inset was tested as a means of mass reduction. FE program ANSYS was used for the analysis (Ansys Theory Reference, 2013, 8).